Psychopathology and Suicide among Quebec Physicians: A Nested Case Control Study. (27th June 2011) - Gagné, Pierre; Moamai, Javad; Bourget, Dominique
Abstract : Objective . To describe a psychiatric profile and characteristics of physicians who killed themselves in Quebec between 1992 and 2009. Method . The cases of 36 physicians (7 females and 29 males) and 36 nonphysicians who committed suicide were matched for age and gender and examined in a nested case control design. All subjects were judged as definite suicide by the Quebec Coroner Head Office. Consensus regarding DSM-IV diagnoses was established by two forensic psychiatrists. Results . Rates of all Axis I diagnoses were 83% for physicians and 91% for nonphysicians at the time of suicide. Major depressive disorders were the most frequently observed pathology in both groups (61% and 56%, resp.). Conclusions . Physicians and nonphysicians who committed suicide in Quebec suffered from the same type of psychiatric disorder at the time of killing themselves. The findings advocate strongly for more efficient suicide prevention measures including early detection and treatment of mood disorders for the physicians.